1994
DOI: 10.1007/bf00040688
|View full text |Cite
|
Sign up to set email alerts
|

The ocs element in the soybean GH2/4 promoter is activated by both active and inactive auxin and salicylic acid analogues

Abstract: The octopine synthase (ocs or ocs-like) element has been previously reported to be responsive to the plant hormones, auxin, salicylic acid, and methyl jasmonate. Using transient assays with carrot protoplasts, we have demonstrated that an ocs element from the soybean auxin-inducible GH2/4 promoter is not only activated by strong auxins (i.e., 2,4-dichlorophenoxyacetic acid, 2,4,5-trichlorophenoxyacetic acid, alpha-naphthalene acetic acid) and salicylic acid, but also by weak auxin analogues (beta-naphthalene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
0
8

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 53 publications
1
80
0
8
Order By: Relevance
“…Chemical Cues That Induce Transcription through as-1 and TGA1a-as-1 type elements confer gene expression in response to the phytohormones auxin, SA, and MJ, whereas other plant hormones, including the cytokinin benzyl-aminopurine and abscisic acid, are inactive (5,9,20,27,31). In contrast to these results, we found that trans-activation by GAL4-TGA1a⌬bZIP or endogenous TGA factors was induced by either natural (i.e.…”
Section: Sequences That Flank the Bzip Domain Of Tga1a Confermentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical Cues That Induce Transcription through as-1 and TGA1a-as-1 type elements confer gene expression in response to the phytohormones auxin, SA, and MJ, whereas other plant hormones, including the cytokinin benzyl-aminopurine and abscisic acid, are inactive (5,9,20,27,31). In contrast to these results, we found that trans-activation by GAL4-TGA1a⌬bZIP or endogenous TGA factors was induced by either natural (i.e.…”
Section: Sequences That Flank the Bzip Domain Of Tga1a Confermentioning
confidence: 99%
“…It has been previously shown that as-1 and related elements confer transcription in response to biologically active and inactive analogs of auxin, suggesting that this response may involve chemical stress cues (8,20). To further investigate this possibility, we tested the ability of the biologically active auxin 2,4-D and its inactive analog 2,3-D to stimulate transcription from the Ϫ90-CAT reporter.…”
Section: Sequences That Flank the Bzip Domain Of Tga1a Confermentioning
confidence: 99%
See 1 more Smart Citation
“…Such motifs have been collectively referred to as ACGT elements (ACEs, Armstrong et al, 1992;Weisshaar et al, 1991). They have been associated with light regulation of expression of a number of genes encoding proteins associated with photosynthesis (Castresana et al, 1988;Donald and Cashmore, 1990;Giuliano et al, 1988;Meier and Gruissem, 1994) and other light-inducible processes such as flavonoid biosynthesis (Schulze-Lefert et al, 1989), with response to abscisic acid (Marcotte et al, 1989;Mundy et al, 1990;Oeda et al, 1991) auxin (Liu and Lam, 1994) wounding (Rosahl et al, 1986) salicylic acid (Qin et al, 1994;Ulmasov et al, 1994;Zhang and Singh, 1994) and anaerobiosis (DeLisle and Ferl, 1990), and with controlled expression of plant histone genes in relation to cell proliferation (Mikami et al, 1994, Osley, 1991Tabata et al, 1991;Tereda et al, 1993Tereda et al, , 1995Yang et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…These type I11 GSTs are induced by numerous environmental stress conditions, including those arising from pathogen attack (Taylor et al, 1990), oxidative stress (Wingate et al, 1988;Levine et al, 1994;Tenhaken et al, 1995), and heavy metal toxicity (Czarnecka et al, 1988;Hagen et al, 1988;Wingate et al, 1988;Mauch and Dudler, 1993). The type I11 GSTs also play a role in the cellular response to both natural and synthetic auxins (Droog et al, 1993;Hahn and Strittmatter, 1994;Ulmasov et al, 1994Ulmasov et al, , 1995Droog, 1995;Droog et al, 1995). Bz2 encodes a type 111 GST and Bz2 Plant Physiol.…”
mentioning
confidence: 99%